The Relationship Between Students’ Anxiety and Their Speaking Skills In The Eleventh Grade In Jakarta Barat Senior High School In The 2021/2022 Academic Year - Akhmad Haqiqi Ma’mun; Syva Aulia Lestari (Jurnal Kewarganegaraan, 2022)
AbstractThe writer held the research in May at the SMAN 16 Jakarta and SMAN 23 Jakarta. The writer took one class from SMAN 16 and one from SMAN 23 Jakarta in second year-student as a sample in this study. The writer used the quantitative correlation design to analyze the research data. In addition, the writer used two instruments to collect the data research such as questionnaire and, a speaking test. Afterward, the result was analyzed using a pre-requisite test consisting of normality tests, regression, and linearity. The result of normality test was equation Y = 60,08 - 0,27 ð‘¥ð‘–. It means that the data were normally distributed and linear. The writer found the correlation coefficient (r) result between studentsâ€™ anxiety and their speaking skill, which was -0,720. Afterward, the writer interpreted the result by using the interpretation table from Ananda and Fadhli (2018). The result showed a negative relation between studentsâ€™ anxiety and their speaking skills. The writer used a t-test for testing the hypothesis, and the final result was -9,3. Then, the writer compared the result using a ttable with a significance level was 5%. The writer got t-test > t table (-9,3 > -1,99), which means Ha was accepted. Thus, it shows that studentsâ€™ anxiety could influence their speaking skills.Keywords: Anxiety, Speaking, English Speaking Skills.